The Mr. Big technique on trial by jury - Connors, Christina J. (Psychology, crime & law, 2019)
Mr. Big is a Canadian undercover police technique used to elicit confessions. Undercover officers befriend the suspect, and gradually draw them into a fictitious criminal organization. Upon meeting the boss of the organization, ‘Mr. Big’, the suspect is pressured to confess. When evidence from the sting operation, including the confession, is presented later in court, it may induce juror moral prejudice towards a defendant. We evaluated how situational and dispositional sting factors (crime task severity, financial incentive, and defendant intelligence) influence mock juror moral prejudice and decision-making in Mr. Big cases. Results from Experiment 1 (N = 270) showed fewer guilty verdicts in the high incentive conditions. In Experiment 2 (N = 1,666), high incentive and low defendant intelligence were related to fewer guilty verdicts, more favorable ratings of defendant character, and more skeptical evaluations of confession evidence. Additionally, there were differences between community and student participants on multiple outcomes.